Employees' physical exercise, resources, engagement, and performance : a cross-sectional study from HERO model - Beltrán, Ester Gil (Colegio Oficial de Psicólogos de Madrid, 2020)
The purpose of this study is to analyze the mediating role of work engagement in the relationship between resources and performance, and the invariance of the HEalthy & Resilient Organizations model (HERO) depending on physical exercise. Moreover, the study examines whether there are differences in the perception of these variables based on workout and gender. The sample consisted of 319 employees (156 sedentary and 163 non-sedentary employees). The results show that engagement mediates between resources and performance in both groups, which demonstrates the invariance of the model. Additionally, the findings revealed that, generally speaking, non-sedentary people are more empathetic and more absorbed in their job tasks and, specifically, that non-sedentary men are more empathetic and more vigorous at work than sedentary men. No differences were found between sedentary and non-sedentary women. Finally, regarding gender differences in variables, women are more empathetic and have better performance than men.